A biblioteca como agente de inclusão social: estudo de caso na Biblioteca Comunitária Bruno Fenzl, Mosqueiro / Pará - SANTOS, Noélia Azevêdo dos (2017)
Approaches the community library as an agent of social inclusion for the community of Mosqueiro / PA. Its general objective is to analyze how the Bruno Fenzl Community Library has contributed to the social inclusion of young people and children through their projects to encourage reading and social interaction. This study opted for a descriptive methodology and made use of two methods "quali quanti". The data were collected through questionnaires applied to volunteers and collaborators of the Ampliar Institute where the Bruno Fenzl Community Library is inserted. It was observed the importance of this as a mediator, disseminator of reading practices, cultural activities and development of the local community, despite some deficiencies, we conclude that the information unit has been playing its social role to include and offer better People living in their environment.